All the world wide web's a stage: The performance of identity in online social networks - Pearson E (Massey University)
This paper discusses how ideas of performance can be used to conceptualize the play of identity formation on social networking sites (SNS). Linking Goffman's theories of social performance with Granovetter's notion of the social tie, this paper will argue that identities on SNS are deliberately constructed performances that straddle the frontstage and the backstage, the public and the private, and in doing so both support and rely upon webs of social connections which engage with fluid or playful identity constructions.
Keywords: 0806 Information Systems; 0807 Library and Information Studies; 2001 Communication and Media Studies